Improved driver behaviour at bus stops on local roads: Comparison of different treatments. (November 2022) - Almallah, Mustafa; Hussain, Qinaat; SayedMohammed, Shabna; Alhajyaseen, Wael K.M.
Highlights: Physical treatment motivated 94.3 % of drivers to avoid overtaking the bus. Approach speed significantly affects the probability of overtaking the bus. Physical and LED stimulated drivers' speed even in the absence of the bus. Physical and LED are recommended to improve safety at bus stops. Abstract: Every day, millions of students use school bus as a mean of transportation to and from schools. Nevertheless, most of the school bus related crashes occur at or near bus stops. The overtaking of stopped school buses during boarding and alighting of students imposes safety risks on students and drivers. This study aims to investigate the impact of three different treatments on driving behavior at bus stops. In total, this study compared four different conditions. Three of them were treatment conditions namely (Red Pavement, Road Narrowing, and smart LED), which were compared with a control condition (i.e., the default bus stop layout without any additional treatments as implemented in the State of Qatar). Each condition was tested for three situations. Situation 1 and Situation 2 were designed with the presence of a stopped school bus on the same and on the opposite travel directions, respectively, while, Situation 3 was designed without any school bus at the bus stop location. A total of 72 subjects participated in the experiment. Generalized Linear Mixed Model (GLMM) was employed to study the impact of several factors on the overtaking/crossing probability of the stopped school bus. In Situation 1, Road_narrowing condition outperformed the other conditions by making 94.3 % of drivers to stop for the bus, while in Situation 2, LED condition performed best by making 48.6 % of drivers stop for the bus that is stopped at the opposite travel direction. Moreover, the LED and Road_narrowing treatments were effective in moderating drivers' speed behavior, lowering their traveling speed by 5.16 km/h and 5.11 km/h, respectively even in the absence of any bus at the bus stop. Physical road narrowing condition outperformed the other tested conditions, and therefore, can be recommended as a low-cost treatment to improve safety at bus stops. In locations where the implementation of physical road narrowing is not feasible, LED treatment can be used to moderate driver traveling speed and stopping behavior.